Commissioning and performance of the Belle II pixel detector - Ye, Hua; Abudinen, F.; Ackermann, K.; Ahlburg, P.; Albalawi, M.; Alonso, O.; Andricek, L.; Ayad, R.; Babu, V.; Bilka, T.; Boronat, M.; Bozek, A.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
The Belle II experiment at the SuperKEKB energy-asymmetric e+e− collider has completed a series of substantial upgrades and started collecting data in 2019. The experiment is expected to accumulate a data set of 50 ab−1 to explore new physics beyond the Standard Model at the intensity frontier. The pixel detector (PXD) of Belle II plays a key role in vertex determination. It has been developed using the DEpleted P-channel Field Effect Transistor (DEPFET) technology, which combines low power consumption in the active pixel area and low intrinsic noise with a very small material budget. In this paper, commissioning and performance of the PXD measured with first collision data are presented.
Available online 18 November 2020
Gesehen am 04.02.2022